2003
DOI: 10.1002/j.2048-7940.2003.tb02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Video Intervention on Functional Recovery Following Hip Replacement and Hip Fracture Repair

Abstract: Although much research has documented the functional outcomes in hip repair surgery, few studies have identified effective interventions to improve functional outcomes. The purpose of this study was to test the use of generic and individualized videos on patients' return to preoperative levels of independent functioning, increased physical performance, improved coping ability, and enhanced perception of ability to care for self. Two rehabilitation units in separate acute care facilities were used to recruit su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
(28 reference statements)
2
27
0
Order By: Relevance
“…The data analyzed in this study were from a study evaluating the impact of postsurgical video-based education that was approved by the University Institutional Review Board (Tappen, Whitehead, Folden, & Hall, 2003). The data analyzed in this study were from a study evaluating the impact of postsurgical video-based education that was approved by the University Institutional Review Board (Tappen, Whitehead, Folden, & Hall, 2003).…”
Section: Designmentioning
confidence: 99%
“…The data analyzed in this study were from a study evaluating the impact of postsurgical video-based education that was approved by the University Institutional Review Board (Tappen, Whitehead, Folden, & Hall, 2003). The data analyzed in this study were from a study evaluating the impact of postsurgical video-based education that was approved by the University Institutional Review Board (Tappen, Whitehead, Folden, & Hall, 2003).…”
Section: Designmentioning
confidence: 99%
“…Educational interventions within these areas have increasingly used sophisticated technology such as computerized multimedia programs that are enriched with video examples. For example, Tappen, Whitehead, Folden, and Hall (2003) used video intervention to prepare patients for hip repair surgery and found that patients who viewed videos showed improved postphysical performance relative to a control group.…”
mentioning
confidence: 97%
“…To the best of our knowledge, this is the first non‐randomized controlled trial designed to analyze the effects of an online platform designed specifically for the rehabilitation of patients with a hip fracture. Only a few previous studies have been carried out to evaluate the effects of tele‐rehabilitation in patients with a hip fracture (Bedra & Finkelstein, ; Tappen et al, ). Tappen et al (), in a quasi‐experimental study with 82 patients, examined the use of explanatory videos to help patients perform physical exercises at home and provide educational information on the performance of ADLs, finding a slight, statistically insignificant improvement in self‐care and functional ability.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been used as a therapeutic intervention for patients following knee arthroplasty (Moffet et al, ), breast cancer surgery (Lozano‐Lozano et al, ), and stroke (Chen et al, ). Nevertheless, the evidence for the use of tele‐rehabilitation in patients with hip fracture is still limited (Bedra & Finkelstein, ; Tappen, Whitehead, Folden, & Hall, ). Some studies involved phone calls to monitor patients at home (Chen et al, ; Tappen et al, ), but the use of websites to provide tele‐rehabilitation for patients with hip fracture is rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation